2020
DOI: 10.1186/s12937-020-00639-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing intake and consumption level of spices among urban and rural households of Ludhiana district of Punjab, India

Abstract: Background Spices are the esoteric food adjuncts that are used for enhancing the sensory quality of the food in Punjabi diets and add many health benefits. Estimating the intake of spices at the individual level is a challenging task as they are consumed in very small quantities as compared to other foods. The present study aimed to assess the intake and spices consumption level of spices among urban and rural households. Methods A study was carried out among 100 households each from urban and rural areas fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The prevalence of neurological diseases in countries that consume more turmeric has been investigated (Ganguli et al, 2000;Ng et al, 2006). Turmeric and red chilies are the most commonly used spices in Indian households (Bhathal et al, 2020;Siruguri & Bhat, 2015), where the average intake can be as high as 2000-2500 mg/day (Basnet & Skalko-Basnet, 2011). Comparisons of the elderly in Eastern and Western populations have shown that frequent consumption of dietary curcumin in India may be linked to a lower risk of Alzheimer's disease and a delay in age-related cognitive impairments than North American populations (Ganguli et al, 2000;Ng et al, 2006).…”
Section: Nutraceutical Approach To Pd Treatment and Preventionmentioning
confidence: 99%
“…The prevalence of neurological diseases in countries that consume more turmeric has been investigated (Ganguli et al, 2000;Ng et al, 2006). Turmeric and red chilies are the most commonly used spices in Indian households (Bhathal et al, 2020;Siruguri & Bhat, 2015), where the average intake can be as high as 2000-2500 mg/day (Basnet & Skalko-Basnet, 2011). Comparisons of the elderly in Eastern and Western populations have shown that frequent consumption of dietary curcumin in India may be linked to a lower risk of Alzheimer's disease and a delay in age-related cognitive impairments than North American populations (Ganguli et al, 2000;Ng et al, 2006).…”
Section: Nutraceutical Approach To Pd Treatment and Preventionmentioning
confidence: 99%
“…Spices are used in different Mediterranean food recipes to impart aroma, color, and taste to food preparations and sometimes mask undesirable odors ( 14 ). Spices refer to the dried part of a plant that contains volatile oils or aromatic flavors such as buds (cloves), bark (cinnamon), root (ginger), berries (black pepper), seeds (cumin, coriander) ( 15 , 16 ).…”
Section: Spices In the Mediterranean Diet: Flavor Characteristics And...mentioning
confidence: 99%
“…Rosemary ( Rosmarinus officinalis ), an aromatic herb that has been known from ancient times as a memory herb, a native to the Mediterranean from Spain to the Balkans and into North Africa ( 14 , 19 ). At present, rosemary is widely cultivated in Spain, Morocco, Tunisia, France, Algeria, Portugal, and China ( 20 ).…”
Section: Spices In the Mediterranean Diet: Flavor Characteristics And...mentioning
confidence: 99%
“…Jowar (sorghum) was the first-choice food grain among the commoners in 19th-century Deccan . For the figure of spice, see Srivastava (2017), Bhathal et al (2020) and that of salt, see Maxham (2001) and Johnson et al (2019).…”
Section: Welfare Levelsmentioning
confidence: 99%